The effectiveness of the multimedia educational manual "Cardiac and Vascular Auscultation" — a new era of digital didactics in internology - A. A. Garanin; A. O. Rubanenko; R. M. Garanina; Yu. A. Trusov (Кардиоваскулярная терапия и профилактика)
Aim. To evaluate the effectiveness of the multimedia manual "Cardiac and Vascular Auscultation" in teaching medical students during Internal Medicine course.Material and methods. A cross-sectional experimental study was conducted, which included 165 students of the Samara State Medical University. All students were divided into two following groups: Group 1 consisted of 93 students who, along with traditional training using the methodological materials available in the university library, were offered to use the developed multimedia manual on cardiac and vascular auscultation during a clinical practical lesson for 30 minutes under the supervision of a teacher. Group 2 consisted of 72 students who were trained according to the traditional method using the methodological materials available in the university library.Results. Electronic testing on cardiac and vascular auscultation for students of both groups showed that in group 1 the median of correct answers was 10 [8; 13], and in group 2 — 8 [5; 11] (p=0,0003). Thus, students in group 1 showed 20% more correct answers compared to students in group 2.Conclusion. The use of the didactic development "Cardiac and Vascular Auscultation" has demonstrated high efficiency in teaching students during Internal Medicine course.